(untitled) - Library of Congress; Legislative Reference Service (Washington, 1946)
This book introduce coommunism Soviet union from the revolution to the 5 year plan, the operation of the Soviet productive system, the role of managemt, labor, forced labor, living standards, agriculture, finance, transportation and communication. Soviet political and social.
Keywords: Chủ nghĩa Cộng Sản,Communism; Liên Xô,Soviet Union